A broken thing : poets on the line - Rosko, Emily, 1979-; Vander Zee, Anton (University of Iowa Press, 2011)
℗¡In the arena of poetry and poetics over the past century, no idea has been more alive and contentious than the idea of form, and no aspect of form has more emphatically sponsored this marked formal concern than the line. But what, exactly, is the line? Emily Rosko and Anton Vander Zee's anthology gives seventy original answers that lead us deeper into the world of poetry, but also far out into the world at large: its people, its politics, its ecology. The authors included here, emerging and established alike, write from a range of perspectives, in terms of both aesthetics and identity.